Vpliv telesne vadbe na reproduktivni sistem moških - Šorli, Diona (Šport (Ljubljana), 2023)
The male reproductive system is influenced by many factors, which may be external or lifestyle-related. Certain factors can affect sperm parameters acutely, while others have more lasting effects. It is well known that certain lifestyle habits have a negative effect on the reproductive system, but it is less well known that excessive and insufficient physical activity can also have a severe impact on reproduction. In the article, we presented the anatomical and physiological features of the male reproductive system and the problem of male infertility. We described the influence of different types, volume and intensity of exercise on the hormonal profile and semen characteristics in men. In addition, we have shortly described the consequences of anabolic androgenic steroid use, the impact of intense physical activity on puberty and the development of young athletes, oxidative stress and its impact on infertility, the most common pathologies of the male reproductive system and the impact of diet on the reproductive system.
Keywords: anabolni androgeni steroidi; erektivna disfunkcija; moški; neplodnost; reproduktivni sistem; šport; telesna aktivnost; testosteron; varikokela